Economic and statistical analysis of food production processes in the Surkhandarya region industry - Khursanov Sherzod Ulaboyevich, (THE INNOVATION ECONOMY, 2026)
the article presents an economic and statistical analysis of the volume of food industry products, non-food industry products, and the volume of consumer goods per capita in Surkhandao region. The basic and chain-like methods were used to analyze the dynamics of the volume of food products. The scientific research works of foreign scientists were also analyzed